The effects of attention deficit/hyperactivity disorder on adolescents exposed to peer victimization - Karatoprak, Serdar; Akyildiz, Abdulbaki; Dönmez, Yunus Emre (Annals of Medical Research, 2022)
Aim: Peer victimization is more common in adolescents with ADHD. Since more internalizing behaviors, externalizing behaviors and academic problems are observed in adolescents exposed to peer victimization, these problems may occur more severely in adolescents with ADHD who are exposed to peer victimization. In this study, it was aimed to investigate the effects of ADHD on internalizing and externalizing behaviors, depression, academic problems in adolescents with ADHD who were exposed to peer victimization. Materials and Methods: This cross-sectional study was conducted with 169 adolescents. Participants completed Socio-demographic Data Form, Olweus Bully/Victim Questionnaire, Strengths and Difficulties Questionnaire-Adolescent Form and Children’s Depression Inventory. The diagnosis of ADHD was determined according to the diagnostic criteria in DSM-V. Results: The study was completed with 41 adolescents with ADHD exposed to peer victimization, 69 adolescents without ADHD exposed to peer victimization, 59 adolescents without ADHD and were not exposed to peer victimization. There was no statistically significant difference between groups in terms of sociodemographic characteristics. School absenteeism was more common in ADHD group. Externalizing behaviors were found to be statistically significantly higher in the ADHD group. Conclusion: The results of this study have revealed that adolescents with ADHD who are exposed to peer victimization exhibit more severe externalizing behaviors. Therefore, ADHD should be specifically investigated in adolescents exposed to peer victimization who develop more severe externalizing behaviors.